The two echelon open location routing problem: Mathematical model and hybrid heuristic. (July 2018) - Pichka, Khosro; Bajgiran, Amirsaman H.; Petering, Matthew E.H.; Jang, Jaejin; Yue, Xiaohang
Highlights: We explore a new problem: the two echelon open location routing problem (2E-OLRP). We formulate three mixed-integer linear programming models of the problem. A hybrid simulated annealing heuristic is developed to solve large problem instances. The proposed heuristic produces solutions that, on average, are within 7.9% of optimal. Abstract: Multi echelon distribution systems have become more common in recent years. This paper addresses the two echelon open location routing problem (2E-OLRP) which is a variant of the two echelon location routing problem (2E-LRP). This problem seeks to find a minimum-cost set of vehicle routes that do not return to the depot in the first echelon and do not return to satellites in the second echelon due to the presence of individual contractors and third party logistics (3PL) providers. In spite of the large amount of research on LRPs, the 2E-OLRP has received very little attention. Three flow-based mixed-integer linear programs and a hybrid heuristic algorithm are proposed to deal with this problem. Extensive experiments evaluate the effectiveness of these methods.